The Role of School Accreditation in Improving the Quality of Graduates - Wahira, Wahira; Hamid, Abd (Journal of Education Method and Learning Strategy, 2023)
This paper aims to describe the role of school accreditation in improving the quality of graduates and inhibiting factors in retaining the quality of graduates. The study used a Literature Review approach by comparing school accreditation data from the accreditation documents of several schools. Based on the results of a literature study from journal articles describing the role of school accreditation in improving the quality component of graduates in the excellent category, the constraint factor is the lack of student filtration, numeracy skills, and teacher competence. Based on the results of the literature review, the author concludes that the role of accreditation in improving the quality of graduates has a vital role in improving the quality of graduates.